2005
DOI: 10.1002/hep.20533
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding protein modulates acetaminophen-induced liver injury in mice

Abstract: Acetaminophen toxicity is the most common cause of acute liver failure in the United States and Europe. Although much is known about the metabolism of acetaminophen, many questions remain regarding the pathogenesis of liver injury. In this study, we examined the role of lipopolysaccharide-binding protein (LBP), a protein important in mediating cellular response to lipopolysaccharides, by using LBP wild-type and knockout (KO) mice. We found that LBP KO mice were protected from acetaminophen-induced hepatotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…The present findings are also consistent with recent observations in patients with advanced cirrhosis and ascites where elevated LBP levels have been found to correlate with marked immune and hemodynamic derangement (2) and increased susceptibility to severe infectious complications (1). In addition, previous work by our group has demonstrated that LBP also contributes to increased hepatic injury and death following acetaminophen-induced liver injury (34). Taken together, this suggests that the presence of underlying liver pathology may alter the effect of LBP on LPS signaling, leading to a predominantly stimulatory rather than inhibitory immune response with acute-phase levels of LBP.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings are also consistent with recent observations in patients with advanced cirrhosis and ascites where elevated LBP levels have been found to correlate with marked immune and hemodynamic derangement (2) and increased susceptibility to severe infectious complications (1). In addition, previous work by our group has demonstrated that LBP also contributes to increased hepatic injury and death following acetaminophen-induced liver injury (34). Taken together, this suggests that the presence of underlying liver pathology may alter the effect of LBP on LPS signaling, leading to a predominantly stimulatory rather than inhibitory immune response with acute-phase levels of LBP.…”
Section: Discussionsupporting
confidence: 93%
“…Blind analysis was performed on all samples to determine the degree of lesion as previously described [15]. The percentage of necrosis was estimated by evaluating the number of microscopic fields with necrosis compared with the entire cross section.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, different innate immune system knockout or mutant mice have been shown to have altered susceptibility to APAP hepatotoxicity. Knockout or mutant mice that lack IFN-g, lipopolysaccharide-binding protein, Fas or FasL, or CXC chemokine receptor 2 (CXCR2) are less susceptible to APAP hepatotoxicity [69,[74][75][76]. Knockout mice that lack IL-10, IL-6, or C-C chemokine receptor 2, however, are more susceptible [77][78][79].…”
Section: Role Of Innate Immune System In Acetaminophen Hepatotoxicitymentioning
confidence: 97%